Lattice separation and measures - James Ponnley (International Journal of Mathematics and Mathematical Sciences)
The effects of lattice separation such as normality, almost normal, slightly normal on various lattice-derived measure are investigated and generalizations of earlier work on 0-1 valued measures are obtained.